If a,b,c are the p th , q th and r th terms respectively of an Arithmetic progression(A.P) . Find the value of a(q-r) + b(r-p) + c(p-q) . Please follow me for more problems like this.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let a = g + d ( p − 1 ) , b = g + d ( q − 1 ) , c = g + d ( r − 1 ) So, the expression of interest is: ( g + d ( p − 1 ) ) ( q − r ) + ( g + d ( q − 1 ) ) ⋅ ( r − p ) + ( g + d ( r − 1 ) ) ( p − q ) = g ⋅ ( q − r + r − p + p − q ) + d ⋅ [ ( p − 1 ) ( q − r ) + ( q − 1 ) ( r − p ) + ( r − 1 ) ( p − q ) = g ⋅ ( 0 ) + d ⋅ [ p q − q − r + r + q r − p q − r + p + r p − q r − p + q ] = 0 + d ⋅ ( 0 ) = 0